2010
DOI: 10.1186/1471-2172-11-38
|View full text |Cite
|
Sign up to set email alerts
|

Intensive chemotherapy for acute myeloid leukemia differentially affects circulating TC1, TH1, TH17 and TREG cells

Abstract: BackgroundSeveral observations suggest that immunological events early after chemotherapy, possibly during the period of severe treatment-induced cytopenia, are important for antileukemic immune reactivity in acute myeloid leukemia (AML). We therefore investigated the frequencies of various T cell subsets (TC1, TH1, TH17) and CD25+ FoxP3+ TREG cells in AML patients with untreated disease and following intensive chemotherapy.ResultsRelative levels of circulating TC1 and TH1 cells were decreased in patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 40 publications
5
52
2
Order By: Relevance
“…91 ) and T-cell chemotactic cytokines 20,92 . Surprisingly, the levels of circulating Th17 cells were not confirmed to be increased in untreated AML patients 93 , which is in contrast to a previous study 94 , possibly due to different mean age of patients enrolled. On the other hand, Th17 cells are not depleted during conventional chemotherapy and circulating Th17 cells can be detected even in periods of severe chemotherapy-induced lymphopenia 93 , so that suf-ficient pre-transplant levels of Th17 cells may be expected.…”
Section: Cytokines In Allogeneic Bone Marrow Transplantationcontrasting
confidence: 55%
See 1 more Smart Citation
“…91 ) and T-cell chemotactic cytokines 20,92 . Surprisingly, the levels of circulating Th17 cells were not confirmed to be increased in untreated AML patients 93 , which is in contrast to a previous study 94 , possibly due to different mean age of patients enrolled. On the other hand, Th17 cells are not depleted during conventional chemotherapy and circulating Th17 cells can be detected even in periods of severe chemotherapy-induced lymphopenia 93 , so that suf-ficient pre-transplant levels of Th17 cells may be expected.…”
Section: Cytokines In Allogeneic Bone Marrow Transplantationcontrasting
confidence: 55%
“…These observations suggest that Th17 cells are important in GvHD development. As the IL-17 itself has only minor anti-proliferative effect on AML blasts, which was observed only in a minority of patients 93 , its role seems to be initially in immunomodulation. The results mentioned above indicate, that Th17 cells enhancement should be considered at high risk of AML relapse with no clinical GvHD, whereas Th17 cells inhibition or depletion may be useful in treatment of excessive GvHD.…”
Section: Cytokines In Allogeneic Bone Marrow Transplantationmentioning
confidence: 99%
“…35, [74][75][76][77] Szczepanski et al demonstrated that 31 AML patients had a greater CD4 ϩ CD25 hi Treg percentage in PB at diagnosis compared with healthy control patients. 35 Tregs from patients with These studies revealed that patients with AML had higher Treg levels compared with HC.…”
Section: Nontransplantation Studiesmentioning
confidence: 99%
“…In previous studies, elevated percentages or levels of Treg cells were reported in the total T-cell population isolated from tumor tissues or peripheral blood in a variety of hematological malignancies, including B-cell non-Hodgkin lymphoma (17), Hodgkin lymphoma (18), chronic lymphocytic leukemia (19)(20)(21), multiple myeloma (22) and AML (5)(6)(7)(8). Treg cells accumulating in the peripheral circulation of AML patients mediate vigorous suppression via IL-10 and TGF-β as well as contact-dependent mechanisms (6).…”
Section: Cytokinementioning
confidence: 99%
“…However, little is known about the pathogenic events leading to the initiation and progression of this disease. Previously, elevated levels of regulatory T (Treg) cells in a variety of hematological malignancies including AML have been reported (5)(6)(7)(8). Patients with a lower Treg cell frequency at diagnosis have a better response to induction chemotherapy and a favorable prognosis (6,8).…”
Section: Introductionmentioning
confidence: 99%